Electron transfer induced decomposition in potassium–nitroimidazoles collisions: An experimental and theoretical work - Mendes, Mónica (2020)
PD/BD/106038/2015 UID/FIS/00068/2019 PTDC/FIS-AQM/31281/2017 PD/00193/2012 project no. FIS2016-80440